In vivo imaging of tau pathology using multi-parametric quantitative MRI - Wells, J.A.; O'Callaghan, J.M.; Holmes, H.E.; Powell, N.M.; Johnson, R.A.; Siow, B.; Torrealdea, F.; Ismail, O.; Walker-Samuel, S.; Golay, X.; Rega, M.; Richardson, S.; et al. (NeuroImage (Orlando, Fla.), 2015)
As the number of people diagnosed with Alzheimer's disease (AD) reaches epidemic proportions, there is an urgent need to develop effective treatment strategies to tackle the social and economic costs of this fatal condition. Dozens of candidate therapeutics are currently being tested in clinical trials, and compounds targeting the aberrant accumulation of tau proteins into neurofibrillary tangles (NFTs) are the focus of substantial current interest. Reliable, translatable biomarkers sensitive to both tau pathology and its modulation by treatment along with animal models that faithfully reflect aspects of the human disease are urgently required. Magnetic resonance imaging (MRI) is well established as a valuable tool for monitoring the structural brain changes that accompany AD progression. However the descent into dementia is not defined by macroscopic brain matter loss alone: non-invasive imaging measurements sensitive to protein accumulation, white matter integrity and cerebral haemodynamics probe distinct aspects of AD pathophysiology and may serve as superior biomarkers for assessing drug efficacy. Here we employ a multi-parametric array of five translatable MRI techniques to characterise the in vivo pathophysiological phenotype of the rTg4510 mouse model of tauopathy (structural imaging, diffusion tensor imaging (DTI), arterial spin labelling (ASL), chemical exchange saturation transfer (CEST) and glucose CEST). Tau-induced pathological changes included grey matter atrophy, increased radial diffusivity in the white matter, decreased amide proton transfer and hyperperfusion. We demonstrate that the above markers unambiguously discriminate between the transgenic group and age-matched controls and provide a comprehensive profile of the multifaceted neuropathological processes underlying the rTg4510 model. Furthermore, we show that ASL and DTI techniques offer heightened sensitivity to processes believed to precede detectable structural changes and, as such, provides a platform for the study of disease mechanisms and therapeutic intervention. •The rTg4510 mouse model exhibits specific tau pathology.•This enables dissection of the unique role of tau in Alzheimer's Disease.•We applied five quantitative, non-invasive MRI techniques to the rTg4510.•We demonstrate the sensitivity of each to discriminate regions of high tau burden.•This study provides a platform for the longitudinal assessment of tau therapies.